APPLICATION OF MEDIA IN THE CONTENT OF THE DISCIPLINE "FOREIGN LANGUAGE EDUCATION: FOREIGN LANGUAGE WITH TEACHING METHODS" - Petryk, Lada (Educological discourse, 2021)
The article describes an experimental study aimed at determining the effectiveness of the use of media in the formation of foreign language communicative competence of future primary school teachers on the example of the discipline "Foreign language education: a foreign language with teaching methods." The concept of "media" is considered as objects, equipment and materials that ensure the functioning of the media information space in the form of audio, visual, audio and visual messages and are allocated by the teacher to organize an active process of learning a foreign language. It is noted that the choice of media was in accordance with the practical objectives of the training sessions. The procedural and effective components of the ascertaining and forming stages of the experiment are analyzed. It is noted that the developed diagnostic tools allowed to conduct diagnostic testing, to determine insufficiently formed foreign language communicative competence of future primary school teachers and to update the formative experiment to test the effectiveness of media in foreign language teaching. It is noted that the content of the discipline was updated with topics, issues related to the analysis, evaluation and use of various types of media, which contributed to the use of modern teaching methods and technologies. A comprehensive survey of students on their awareness of the impact of media on the effectiveness of learning a foreign language and the formation of their media skills is also analyzed. The dynamics of the levels of formation of foreign language communicative competence of future primary school teachers, that also affected the quality of student achievement is demonstrated in the paper.